How Refugees’ Stereotypes Toward Host Society Members Predict Acculturation Orientations: The Role of Perceived Discrimination - Lutterbach, Sebastian; Beelmann, Andreas (Frontiers in Psychology, 2021)
Refugee migration leads to increased diversity in host societies and refugees have to face many stereotyped attitudes in the host society. However, there has been little research on minority group stereotypes toward host society members and how these stereotypes relate to the acculturation-relevant attitudes of refugees in their first phase of acculturation. This study surveyed 783 refugees in Germany who had migrated mostly in the so-called “refugee crisis” between 2015 and 2016. At the time of the survey in 2018, they had been in Germany for an average of 27 months (SD = 15 months). These refugees reported their positive and negative sociability stereotypes toward German host society members, acculturation-related orientations, shared reality values, and perceived discrimination. Results showed that positive sociability stereotypes toward host society members were associated with increased cultural adoption and shared reality. In contrast, negative sociability stereotypes negatively affected cultural adoption and shared reality. However, stereotypes showed no association at all with cultural maintenance. Interactions between sociability stereotypes and discrimination experiences highlighted a disillusion effect, in the sense that discrimination reduced the motivation to adopt the host culture more strongly among refugees who held strongly positive sociability stereotypes. The study extends knowledge on the significance of minority group stereotypes in the context of refugee migration and reveals the maladaptive consequences of discriminatory behavior against refuges by host society members.